IDEOLOGI SEKULARISME DALAM KOMENTAR MASYARAKAT TENTANG WACANA PILKADA DKI JAKARTA DI MEDIA SOSIAL - Liza Halimatul Humairah; Agustina Agustina; Ngusman Abdul Manaf (Universitas Negeri Makassar, 2019)
Abstract: The Ideology of Secularism in the Public Comment on the Discourse of DKI Jakarta Pilkada on Social Media. This study aims to determine the realization of secularism in the public comment text on the DKI Jakarta Pilkada news discourse on social media in terms of vocabulary and sentence structure. This study uses a qualitative-descriptive approach and content analysis method based on Norman Fairclough's theory of critical discourse. The results of the study show that the ideology of secularism is realized: (1) using words that are not related to religion such as the words smart, objective, rational, not, real work etc. which is associated with context; (2) active sentences, with the aim of further highlighting the actors and objects of events; and (3) passive sentences, with the aim of further highlighting the target and hiding the perpetrator. Ideology in discourse can be expressed through vocabulary choices and sentence structure in text through critical discourse analysis, both in mass media texts, and in individual texts (comments) on social media.